PEMBELAJARAN DARING DALAM UPAYA MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK MELALUI KEGIATAN FUN COOKING KELOMPOK B TK PARIPURNA 3 CIMAHI - Ria Martina Pertiwi; Rita Nurunnisa (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2022)
The research was motivated by the low learning outcomes of language skills in children. In learning activities, educators do not develop language skills, this can be seen from conventional learning by only using the blackboard at school. The process of learning activities does not look child-centered but looks teacher-centered, for that researchers suggest that every teacher carry out learning activities using media so that learning will feel alive and fun for children. This study uses a qualitative descriptive research method with research subjects in group A children of TKQ Madinatul Islam. Data collection techniques: observation, interviews and documentation, data analysis: data reduction, data display, and data verification/conclusion. Learning activities using flannel board media were carried out, based on data analysis at first the children had a little difficulty in using the media but when the teacher gave directions, guidance, and rules for playing the flannel board media, the children became more proficient and looked engrossed in playing the flannel board media, it can be seen when they play letters, say letters, string letters into their names, even with the flannel board media, children can imitate and write their names in their books. The conclusion is that improving language skills in children can be done using flannel board media.Dikarenakan adanya wabah penyakit Covid-19, pemberian stimulasi perkembangan untuk perkembangan kognitif, bahasa, fisik motorik, sosial emosional, agama dan moral serta seni harus dilakukan di rumah masing-masing peserta didik. Aspek perkembangan kognitif adalah aspek utama yang dapat mempengaruhi perkembangan aspek yang lain. Melihat kenyataan di lapangan bahwa begitu beragamnya permasalahan mengenai perkembangan kognitif sesuai dengan variabel anak usia dini apalagi dengan ditambah pembelajarannya dilakukan secara daring. Penelitian ini bertujuan meningkatkan perkembangan kognitif anak dalam pembelajaran daring di TK Paripurna 3 Cimahi melalui kegiatan fun cooking. Penelitian ini dilaksanakan di kelompok B, dengan jumlah anak 10 orang, 7 anak perempuan dan 3 anak laki-laki.Penelitian ini menggunakan metode deskriptif kualitatif dengan tujuan untuk mengetahui peningkatan terhadap perkembangan kognitif anak melalui kegiatan fun cookingpada saat pembelajaran daring.Teknikpengumpulan data yang digunakan peneliti menggunakan teknikobservasi, perekaman,dan wawancara untuk memperjelashasil observasi pembelajaran online,danmeningkatkan perkembangan kognitif anak melalui kegiatan fun cookingkelompok B TK Paripurna 3 Cimahi. Analisis data yang digunakan telahmelalui tahapanreduksi data, penyajian data dan verifikasi data. Melalui hasil penelitian, diperoleh informasi adanya peningkatan perkembangan kognitif anak dalam pembelajaran daring melalui kegiatan fun cookingterutama dalam berfikir logis.